1996
DOI: 10.15288/jsa.1996.57.77
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and social consequences related to the consumption of different beverage types.

Abstract: The purpose of this article is to review the literature on the effects of beer, wine and spirits on the behavioral consequences of alcohol consumption. Method: The methods involve library research and analysis of the various published articles relating to experimental and survey studies of different effects. Results: The major results indicate that (1) after spirits consumption blood alcohol concentrations rise more quickly than after beer; (2) for most behavioral tasks beer creates less impairment than brandy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
8

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 39 publications
7
67
0
8
Order By: Relevance
“…Hence, the determinants of consumption need not be the same for different beverages. It has also been found in previous studies that the beverage type matters with respect to the outcomes of drinking (Smart 1996;Norström 1998).…”
Section: Theoretical Frameworksupporting
confidence: 55%
“…Hence, the determinants of consumption need not be the same for different beverages. It has also been found in previous studies that the beverage type matters with respect to the outcomes of drinking (Smart 1996;Norström 1998).…”
Section: Theoretical Frameworksupporting
confidence: 55%
“…immediate negative consequences, such as fatal automobile accidents (National Highway Traffic Safety Administration, 1997), injuries, and risky sexual behavior (Fergusson and Lynskey, 1996;Quigley and Marlatt, 1996;Smart, 1996;Thakker, 1998, Zucker, 1994. Less is known about more long-term consequences of such use.…”
mentioning
confidence: 99%
“…It can also been argued that either the expectations from spirits consumption (Smart, 1996) or the higher frequency of drunkenness among spirits drinkers (Schimd et al, 2003;Siegel et al, 2011) may expose them to a greater risk of incidents related to alcohol consumption compared to consumers of other alcoholic beverages. At the population-level, Kerr and Ye (2011) have confirmed that spirits sales were predominately associated with alcohol-related mortality in the U.S., which supports the differential treatment given to spirits in terms of taxation and availability policies compared to beer or wine in this country.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, drinkers who prefer beer are more likely to drink heavily and to be involved in drinking-driving injuries (Smart, 1996;Jensen et al, 2002), while wine drinking has not shown a significant association with the occurrence of alcoholrelated injuries (Smart, 1996;Watt et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation